Between Survival and Sustenance : Plants for Recycle Edible Garden - Mohd Hussain, Nur Huzeima; Amir, Atikah Fukaihah; Mt Akhir, Norizan; Ibrahim, Khairul Adham (Environment-Behaviour Proceedings Journal, 2018)
Previous studies demonstrate that plants played a significant role in the edible garden plantings.Â Therefore, this study aims to analyse and evaluate the practicality and performance of plants selected in composing the recycle edible garden at Masjid As-Siddiq. This paper discusses the issues, challenges and imperatives of how a successful plants selection would lead towards survival and sustenance food for the community. The data derived from qualitative and quantitative method through photo and images recorded throughout the implementation period.Â The results will interpret relevant information about the plants potential in surviving and becoming sustenance towards the sustainable community.Â